Pressure-controlled luminescence in fast-response barium fluoride crystals - Marilou Cadatal-Raduban; Luong Viet Mui; Masahiro Yamashita; Yuki Shibazaki; Toshihiko Shimizu; Nobuhiko Sarukura; Kohei Yamanoi (NPG Asia Materials)
Abstract Cross-luminescence (CL) in a barium fluoride (BaF2) scintillator arising from the recombination of a valence band electron and a core band hole results in a fast picosecond decay time. However, the CL emission wavelength in the vacuum ultraviolet region is difficult to detect, and intrinsically intense and slow nanosecond self-trapped exciton (STE) luminescence occurs. Herein, we report a redshift in the CL emission wavelength with high-pressure application. The wavelength of the CL emission shifted from 221 nm to 240 nm when 5.0 GPa was applied via a sapphire anvil cell. Increasing the pressure decreases the core-valence bandgap due to the downward expansion of the valence band, resulting in a decrease in the valence band minimum. The onset of a phase transition from a cubic crystal structure to an orthorhombic crystal structure at 3.7 GPa inhibited the recombination of conduction band electrons and self-trapped holes, leading to the disappearance of the STE emission. Manipulating the band structure of BaF2 by high-pressure application enables control of its luminescence emission, providing a pathway toward solving the problems inherent in this leading fast-response scintillator.